The Legislative Framework for Working Conditions in the Dutch Ready-Made Garment Sector - Rosalien A. van ‘t Foort-Diepeveen (Yuridika, 2019)
This article sets out the legislative framework with regard to labour law provisions concerning working conditions that apply to Dutch employers and employees operating and working in the ready-made garment (RMG) sector in the Netherlands and discusses the challenges that employees may face in the sector. More specifically, this article will focus on the challenges and law applicable to the retail phase and recycling phase in the supply chain of a pair of jeans and a white T-shirt. In this respect, an overview of the labour law provisions will be presented that protect a safe working environment for employees working in the sector. Dutch law contains many provisions concerning the protection of employees against poor working conditions. Among others, employers are obliged to maintain a safe working environment and reasonable working hours for their employees. Dutch labour legislation only applies to employees working in the Netherlands and therefore is of little relevance to the manufacturing phase of the RMG supply chain, which takes place abroad. However, several public and private initiatives were taken to stimulate Dutch clothing brands to exert an influence on the working conditions in the RMG producing countries. Two of these initiatives will be discussed in this article. Furthermore, this article will present which social challenges employees may face in the Dutch RMG sector, which comprise gender inequality, including equal pay and equal opportunities to occupy top management positions and co-determination rights.